Ideological predictors of anti-science attitudes: exploring the impact of group-based dominance and populism in North America and Western Europe - Remsö, Amanda; Renström, Emma A. (Frontiers in Social Psychology, 2023)
This research examined individual-level ideological variables as predictors of anti-science attitudes, encompassing a lack of acceptance, belief, and trust in science as an institution and source of knowledge. We specifically focused on ideologies associated with group-based dominance and populism while also considering conventional predictors like scientific literacy, symbolic ideology, and partisanship. Study 1 was an original survey (U.S. participants, N = 700), which replicated prior research showing that political conservative identity and attitudes favoring group-based dominance most strongly predicted anti-science attitudes. In contrast, populist attitudes had no substantial effect. In Study 2, analyzing data from the Dutch LISS Panel (N = 2186), group-based dominance attitudes, specifically with regard to gender, as well as populist attitudes and conspiracy beliefs, emerged as the most prominent factors predicting anti-science attitudes. These studies speak to the role of groupbased dominance attitudes in undermining the perceived validity of science, as observed in both North American and Western European samples. Whether these results reflect more consistent patterns or are specific to particular countries and cultural contexts is not clear, emphasizing the need for future research on how these ideologies shape and perpetuate anti-science attitudes.